Service Quality to Customer Loyalty at Vovi Corner Delivery Services During the Covid-19 Pandemic - Anita Dwi Normalianingsih; Denpharanto Agung Krisprimandoyo (Universitas Ciputra Surabaya, 2022)
The lifestyle and high level of busyness of the community as well as the demands in speed and time efficiency make the culinary business considered a great opportunity today. Food Delivery Services participates in supporting the marketing of these culinary business services. The purpose of this study was to determine the effect of service quality on the loyalty of Vovi Corner food delivery customers. The method used in this study is a quantitative method with a total population of 209 people who are vovi corner repeat order customers through an online application. Meanwhile, the research sample was determined based on the sampling formula by Slovin and obtained a sample of 75 people. This study used multiple regression analysis and tested using SPSS software. The results showed that responsiveness has a positive and significant effect on the loyalty of Vovi Corner online food delivery customers. This is evidenced by the attitude of employees who help customers when in doubt in ordering. Meanwhile, tangible, reliability, assurance, and empathy showed insignificant results on the loyalty of Vovi Corner's online food delivery customers.